Ответы и объяснения

Лучший Ответ!
2014-02-23T21:10:33+04:00
(у + 1)* 18 = 36 + 12 * (у +1)
18у +18 = 36 + 12у + 12
6у = 36 - 18 +12
6у = 30
у = 5
________________________
(5 + 1)* 18 = 36 + 12 * (5 +1)
                           108 = 108

(к + 5)* 7 - 54 = (к + 5)* 4
7к + 35 - 54 = 4к + 20
35 - 20 - 54 = 4к - 7к
-39 = - 3к
к = 13
_____________________
(13 + 5)* 7 - 54 = (13 + 5)* 4
                              72 = 72

17* (с - 2) - 36 = 19 + (с - 2)* 12
17с - 34 - 36 = 12с - 24 + 19
17с - 12с = 70 - 5 
5с = 65
с = 13
__________________________
17* (13 - 2) - 36 = 19 + (13 - 2)* 12
                                   151 = 151